EFEKTIVITAS METODE PEMBELAJARAN KOOPERATIF JIGSAW DENGAN BERBANTUAN MEDIA WAYGROUND DALAM MENINGKATKAN PENGUASAAN MUFRADAT SISWA MAN 1 BONE - Misra Asriani; Haeriyyah; Agussalim, Andi; Ridwan, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of implementing the Jigsaw cooperative learning method assisted by the digital media Wayground in improving students’ vocabulary mastery at MAN 1 Bone. The research problem arises from students’ low vocabulary achievement due to the use of conventional teaching methods, which affect their motivation and learning outcomes. This study employed a quantitative approach with a quasi-experimental design using a one-group pretest–posttest model. The sample consisted of 28 eleventh-grade students. A vocabulary test was used as the research instrument after being validated and tested for reliability. The data were analyzed using the Wilcoxon Signed Rank Test because the data were not normally distributed. The findings revealed a statistically significant difference between the pretest and posttest scores, indicating that the Jigsaw method assisted by Wayground is effective in improving students’ vocabulary mastery.